American empire : Roosevelt's geographer and the prelude to globalization - Smith, Neil, 1954-2012 (University of California Press, 2003)
Arguing that American globalism had a very distinct geography and was pieced together as part of a powerful geographical vision, this text explores US global ambition. The story unfolds through an account of the career of Isaiah Bowman, the most famous American geographer of the 20th century.
Keywords: Bowman, Isaiah, -- 1878-1950.; Bowman, Isaiah, -- 1878-1950; Geographers -- United States -- Biography.; Geography -- United States -- History -- 20th century.; Globalization -- History -- 20th century.; Géographie -- États-Unis -- Histoire -- 20e siècle.; Mondialisation -- Histoire -- 20e siècle.; TRAVEL -- Museums, Tours, Points of Interest.; BIOGRAPHY & AUTOBIOGRAPHY -- Adventurers & Explorers.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; TRAVEL -- Hikes & Walks.; TRAVEL -- Budget.; TRAVEL -- Special Interest -- Ecotourism.; TRAVEL -- Parks & Campgrounds.; TRAVEL -- Reference.; TRAVEL -- Road Travel.; TRAVEL -- Special Interest -- Adventure.; HISTORY -- United States -- General.; Geographers; Geography; Globalization; United States; 1900-1999; american empire.; american history.; colonialism.; colonies.; contemporary.; cultural history.; cultural studies.; culture.; debunked.; empire.; europe.; european colonialism.; european colonies.; european history.; explorer.; foreign policy.; geography.; global.; globalism.; globalization.; international.; modern world.; myth.; power structure.; power struggle.; science.; social history.; social studies.; state department.; united nations.; united states history.; us history.; collective biographies.; Biographies; History; Biographies.; Electronic books.